Invisibility in global health: A case for disturbing bioethical frameworks [version 2; peer review: 2 approved, 1 approved with reservations] - Chelsea Modlin; Shu Hui Ng; Jonathan D. Shaffer; Patricia Kingori; Michael Parker; Arsenii Alenichev; Ilana Ambrogi; Marlyn C. Faure; Halina Suwalowska (Wellcome Open Research, 2023)
In recent years, the global health community has increasingly reported the problem of ‘invisibility’: aspects of health and wellbeing, particularly amongst the world’s most marginalized and impoverished people, that are systematically overlooked and ignored by people and institutions in relative positions of power. It is unclear how to realistically manage global health invisibility within bioethics and other social science disciplines and move forward. In this letter, we reflect on several case studies of invisibility experienced by people in Brazil, Malaysia, West Africa and other transnational contexts. Highlighting the complex nature of invisibility and its interconnectedness with social, political and economic issues and trends, we argue that while local and targeted interventions might provide relief and comfort locally, they will not be able to solve the underlying causes of invisibility. Building from the shared lessons of case study presentations at an Oxford-Johns Hopkins Global Infectious Disease Ethics Collaborative (GLIDE), we argue that in dealing with an intersectional issue such as invisibility, twenty-first century global health bioethics could pursue a more ‘disturbing’ framework, challenging the narrow comforting solutions which take as a given the sociomaterial inequalities of the status quo. We highlight that comforting and disturbing bioethical frameworks should not be considered as opposing sides, but as two approaches working in tandem in order to achieve the internationally set global health milestones of providing better health and wellbeing for everyone. Insights from sociology, anthropology, postcolonial studies, history, feminist studies and other styles of critical reasoning have long been disturbing to grand narratives of people and their conditions. To rediscover the ethos of the WHO Alma Ata Declaration—a vision of “health for all by the year 2000”—these thinking tools will be necessary aids in developing cooperation and support beyond the narrow market logic that dominates the landscape of contemporary global health.